Implementation of PPKM Level 2-4 Covid 19 Pandemic of Gunungpati, Semarang City: (Referring to the Regulation of the Mayor of Semarang No. 57 of 2020) - Ari Dwi Astono (Pusat Riset dan Inovasi Nasional, 2022)
The emergence of the current COVID-19 pandemic has a significant impact on people's activities from various aspects of life, both in foreign countries and in this country in various sectors, namely economic, political, social and cultural. The Covid-19 pandemic has hit almost 3 years and has not been fully controlled. Government policies that have been made and implemented require good management, for that full support from the community is also needed. The implementation of existing policies, ranging from PSBB, transitional PSBB, emergency PSBB, New Normal PSBB, Emergency PSBB 2, PPKM, emergency PPKM, Micro PPKM is felt to have not shown a significant decline, this makes the government continue to strive to continue to make policies and regulations. To reduce the rate of suspected Covid-19 contamination, the last government policy through the Java and Bali Level PPKM showed good results, was able to suppress and control the Covid-19 pandemic, Covid-19 control will not work if only the government does it, but requires participation of all elements of society in their respective areas. The government really needs the participation of various parties, namely the business world, the community, Covid-19 volunteers, community leaders and the media. In addition, community behavior is expected to be disciplined in implementing the health protocol, namely 3M (maintaining distance, wearing masks and washing hands frequently), with 3M discipline being the key to strengthening the implementation of 3T (testing, tracing, treatment) down to the village level. In addition, social distancing, long-distance travel restrictions, and proper promotion and education to the public are forms of public health efforts in breaking the chain of the spread of the Corona virus. In fact, there are still people who don't follow the rules, go out on motorbikes, don't wear masks and helmets, don't maintain social distancing, still crowd in the market, they tend to ignore the rules for wearing masks, even though there are rules from PerWali Semarang number 57 of 2020 article 6 paragraph 3